Energy Efficiency of a Vernacular Building Design and Materials in Hot Arid Climate: Experimental and Numerical Approach - Karima El Azhary; Mohamed Ouakarrouch; Najma Laaroussi; Mohammed Garoum (International Journal of Renewable Energy Development, 2021)
Morocco faces tremendous climate constraints; the climate is hot and dry in most parts of the country, and when selecting an energy-saving approach, the architectural landscape becomes essential.Designer and building professionals seem to have neglected this large-scale integration. Sustainable development programs in terms of sustainable architecture are ongoing in countries around the world. One part of this trend is the growing concern shown in the high environmental efficiency of vernacular architecture. It is within this prescriptive framework that this research study is being conducted, which reveals novel architectural style integrating thermal comfort, energy efficient characteristics, passive solar elements architecture, and construction techniques inspired from the vernacular Ksourian architectural configurations. The goal of the present research study is to identify features of energy efficient vernacular architecture and thermal performances that affect indoor thermal comfort conditions for adaptation to current lifestyles in modern architecture. The key characteristics developed are; built mass structure, building orientation, space planning, availability of sunspace, building techniques, and new coating materials for manufacturing and roofing. The suggested methodology enables to analyze the thermal performance analysis, applying an experimental research using experimental testing measurement and comparative optimization processes for thermal efficiency and comfort evaluation of a traditional vernacular earthen house.Series of experimental thermophysical characterization measurements have been carried out in order to quantify on a real scale the thermophysical properties that characterize the Rissani earth. Thusthermophysical characterization results are operated as input data for the thermal dynamic simulation for the purpose to evaluate thermal performances and comfort under the weather conditions and control natural comfort in both summer and winter, without using heating or cooling systems. Ultimately, the simulations carried out make it possible to identify the optimal orientation, revealing an effective decrease in interior temperatures during summer and providing good thermal comfort in winter.